2018
DOI: 10.1002/hpm.2685
|View full text |Cite
|
Sign up to set email alerts
|

The effect of patient satisfaction with academic hospitals on their loyalty

Abstract: SummaryObjectivesPatients' loyalty to a health care institution can lead to the aggregation of patients' medical history in an institution and facilitating access to records by health care providers. Considering the increase of the competition between providers, it is important to gain patients' satisfaction, which leads to their return and loyalty. Therefore, this study evaluated the effect of patients' satisfaction with service quality on their loyalty.MethodsA cross‐sectional descriptive and analytical stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
3
13
0
2
Order By: Relevance
“…A signi cant relationship was observed between service cost and patient satisfaction (coe cient = 0.26), that is, patients are satis ed if they perceive that out-of-pocket payments are reasonable in terms of value and quality. The result matches the ndings of previous studies where service costs were found to be one of the important determinants of patient satisfaction (5,25,29) Accessibility and appointment were recognized as two other factors affecting patient satisfaction. These ndings are reinforced by those of previous studies in which accessibility was an important and determining factor in patient satisfaction (13,30).…”
Section: Discussionsupporting
confidence: 89%
“…A signi cant relationship was observed between service cost and patient satisfaction (coe cient = 0.26), that is, patients are satis ed if they perceive that out-of-pocket payments are reasonable in terms of value and quality. The result matches the ndings of previous studies where service costs were found to be one of the important determinants of patient satisfaction (5,25,29) Accessibility and appointment were recognized as two other factors affecting patient satisfaction. These ndings are reinforced by those of previous studies in which accessibility was an important and determining factor in patient satisfaction (13,30).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, further steps need to be taken to enhance patient-centered principles in primary health care services. 31 , 32 …”
Section: Resultsmentioning
confidence: 99%
“…A satisfação do paciente e a lealdade são construtos consequentes da percepção de valor do serviço (Pevec & Pisnik, 2018). A satisfação foi identificada como tendo um efeito positivo na lealdade do paciente em instituições de saúde (Anabila, 2019;Min et al, 2019;Rostami et al, 2019). Em um desses estudos, os principais determinantes da lealdade foram o custo dos serviços prestados, a avaliação do ambiente, os procedimentos e serviços, o acesso aos provedores de saúde, como equipe médica e de enfermagem, e o fornecimento de informações sobre a assistência (Rostami et al, 2019).…”
Section: Benefícios Ao Paciente: Percepção De Valor Qualidade Do Serviço Experiências Do Paciente Reputação E Confiançaunclassified
“…Ressalta-se que foi encontrada baixa correlação entre o tempo de espera e a lealdade do paciente, ou seja, pacientes que enfrentam maior tempo de espera não relatam desejo de retornar à instituição de saúde e decidem não recomendar a instituição para outras pessoas (Rostami et al, 2019).…”
Section: Benefícios Ao Paciente: Percepção De Valor Qualidade Do Serviço Experiências Do Paciente Reputação E Confiançaunclassified